Hipoksia Intermiten sebagai Pemicu Disfungsi Mitokondria: Tinjauan Naratif Mekanisme Seluler - Dwi Widyawati; Ghea Farmaning Thias Putri (Universitas Sultan Ageng Tirtayasa, 2026)
Intermittent hypoxia is characterized by recurrent cycles of oxygen deprivation and reoxygenation, commonly observed in chronic diseases such as obstructive sleep apnea, respiratory disorders, and metabolic conditions. Compared to continuous hypoxia, it induces more dynamic cellular stress, particularly affecting mitochondrial function. This review aimed to analyze the cellular mechanisms by which intermittent hypoxia triggers mitochondrial dysfunction. A structured narrative literature search was conducted using PubMed, Scopus, ScienceDirect, and Google Scholar. A total of 104 articles were identified, of which 22 met the inclusion criteria and were included in the analysis. Selected studies were descriptively synthesized to identify key mechanisms. Intermittent hypoxia disrupts mitochondrial electron transport chain activity, especially at complexes I and III, leading to electron leakage and increased reactive oxygen species (ROS). Recurrent oxidative stress causes mitochondrial membrane damage, protein oxidation, mitochondrial DNA injury, reduced ATP synthesis, and impaired cellular bioenergetics. It also alters mitochondrial dynamics and weakens antioxidant defenses. Intermittent hypoxia is a major trigger of mitochondrial dysfunction through repetitive oxidative stress, contributing to metabolic disturbances and organ dysfunction.